Quantitative relationship between strain and acoustic emission response in monitoring fatigue damage - Mohammad, Mazian; Abdullah, Shahrum; Jamaludin, Nordin; Inayatullah, Othman (Universiti Teknologi Malaysia Press, 2014)
This study was carried out to investigate the relationship between the strain and acoustic emission (AE) signals, thus, to confirm the capability of AE technique to monitor the fatigue failure mechanism of a steel component. To achieve this goal, strain and AE signals were captured on the steel specimen during the cyclic fatigue test. Both signals were collected using specific data acquisition system by attaching the strain gauge and AE piezoelectric transducer simultaneously at the specimen during the test. The stress loading used for the test was set at 600 MPa, and the specimens were fabricated using the SAE 1045 carbon steel. The related parameters for both signals were determined at every 2000 seconds until the specimen failed. It was found that a meaningful correlation of all parameters, i.e. amplitude, kurtosis and energy, was established. Finally, all AE parameters are correlated with the damage values, which have been estimated using the Coffin-Manson model. Hence, it was suggested that the AE technique can be used as a monitoring tool for fatigue failure mechanism in a steel component.